2003
DOI: 10.2166/wst.2003.0013
|View full text |Cite
|
Sign up to set email alerts
|

How farmers in Switzerland perceive fertilizers from recycled anthropogenic nutrients (urine)

Abstract: We studied acceptance of a urine-based fertilizer product using a mail survey of 467 Swiss farmers. We distinguished among four production types: organic or IP farming, and with or without vegetable production. Considering that the idea of urine-based fertilizers is new, acceptance among the answering farmers was surprisingly high, with 57% explicitly stating that they thought it was a good or very good idea, and 42% willing to purchase such a product. The farmers of different production types did not differ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 9 publications
4
38
0
1
Order By: Relevance
“…In a study conducted in Switzerland, 42% of farmers said they would purchase a "urine-based fertilizer"; 43% were in favor of altering regulations for the approval of this kind of fertilizer, and more than half of them had a positive view of the use of human urine as a fertilizer (Lienert et al 2003). These authors' opinion was that the demand for nutrients by Switzerland's producers could, to a certain degree, be supplied by human urine.…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in Switzerland, 42% of farmers said they would purchase a "urine-based fertilizer"; 43% were in favor of altering regulations for the approval of this kind of fertilizer, and more than half of them had a positive view of the use of human urine as a fertilizer (Lienert et al 2003). These authors' opinion was that the demand for nutrients by Switzerland's producers could, to a certain degree, be supplied by human urine.…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
“…These authors' opinion was that the demand for nutrients by Switzerland's producers could, to a certain degree, be supplied by human urine. One interesting result from the Switzerland study is that 47% (n=34) of farmers report that they would use human urine as a fertilizer even if the origin of the urine was unknown (Lienert et al 2003). Origin is an important factor that needs to be considered.…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of NoMix (26) also considered farmers as stakeholders because the nutrients potentially recovered from urine can be used to produce agricultural fertilizer. The results of the study revealed that farmers would use the urinebased fertilizer so long as it did not cost more than their current fertilizer product nor present any risks to human health.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The use of synthetic mineral fertilizers is not allowed in organic farming, especially with vegetables. Farmers using the IP standard are allowed to use synthetic mineral fertilizer, provided that the nutrient balance on the farm is in equilibrium (Lienert et al 2003). Hence, natural fertilizers are becoming an attractive alternative way to avoid the use of synthetic chemical fertilizers.…”
mentioning
confidence: 99%